Activated carbon from palm kernel shell as an adsorbent of paraquat - Shahjahan, Mohosina Bintay (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2013)
Highly Efficient Activated Carbon (HEAC) as an adsorbent of toxins has been successfully produced from palm shell through chemical activation process using phosphoric acid as an activating agent. Palm Kernel shell used as the main raw material for activated carbon production, was purchased from a local oil palm mill in Pahang, Malaysia. Temperature range 550 ºC – 650 ºC was used during the activation process. The effect of temperature variation on the pore size and surface morphology of the activated carbon were studied. Well developed pore size and low number of functional groups observed on activated carbon at 600 ºC were determined by Scanning Electron Microscope (SEM) and Fourier- Transform Infrared (FTIR) spectroscopy, respectively. The surface area and pore volume were determined by Brunauer, Emmett and Teller (BET) method using N2 gas adsorption. The highest surface area (1287 m2g-1) and pore volume (0.74 cm3 g-1) was observed with sample HEAC-2. The adsorption efficiency of HEAC-2 was studied in vitro for paraquat as toxin using distilled water and NaCl (0.9%) solution. These study shows paraquat was adsorbed more on HEAC-2 in the presence of sodium chloride solution (4.68 mgL-1) than in distilled water (3.62 mgL-1). Furthermore, a comparision was done between HEAC-2 (4.68 mgL-1) and commercially available activated carbon (4.18mg L-1) which proved HEAC-2 is more effective than commercially available activated carbon